Characterization of the complete mitochondrial genome of Mauritian sardinella, Sardinella jussieu (Lacepède, 1803), collected in the Banten Bay, Indonesia - Sinar Pagi Sektiana, ,- (2017)
Fishes in genus Sardinella are small pelagic species, which plays an important role in marine ecosystem as the first consumer. Those species are also commercially important, whose total catch reaches 278,600 tons in 2011 in Indonesia, but their identification has been difficult for their morphological similarity. In this study, we reported Sardinella jussieu for the first time in Indonesian coastal area (Banten Bay, Indonesia, 6° 0′ 50.00″ S–106° 10′ 21.00″ E). We were able to confirm the species by both its morphological characteristics including the black spot at dorsal fin origin, the dusky pigmentation at caudal fin, 31 total scute numbers, and DNA sequence identity in the GenBank database by the molecular analysis. Its total mitochondrial genome was determined by the combination of nextgeneration sequencing and typical PCR strategy. The total mitochondrial genome of Sardinella jussieu (16,695 bp) encoded 13 proteins, 2 ribosomal RNAs, 22 transfer RNAs, and the putative control region. All protein-coding genes started with ATG and typical stop codon and ended with TAA or TAG except for ND4 in which AGA is used. Phylogenetic analyses of both COI region and full mitochondrial genome showed that S. jussieu is most closely related to Sardinella albella and Sardinella gibbosa.